2016
DOI: 10.1117/1.jnp.10.016010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of indium gallium nitride facet-dependent nonpolar growth rates and composition for core–shell light-emitting diodes

Abstract: Abstract. Core-shell indium gallium nitride (InGaN)/gallium nitride (GaN) structures are attractive as light emitters due to the large nonpolar surface of rod-like cores with their longitudinal axis aligned along the c-direction. These facets do not suffer from the quantum-confined Stark effect that limits the thickness of quantum wells and efficiency in conventional light-emitting devices. Understanding InGaN growth on these submicron three-dimensional structures is important to optimize optoelectronic device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…. But within a nanorod geometry, up to four different facets can co‐exist, so that competition between various growth directions occurs. In this study, we have demonstrated that the change in V/III ratio has a major impact on the AlN regrowth along <0001>, <10‐10>, and <11‐20>.…”
Section: Resultsmentioning
confidence: 99%
“…. But within a nanorod geometry, up to four different facets can co‐exist, so that competition between various growth directions occurs. In this study, we have demonstrated that the change in V/III ratio has a major impact on the AlN regrowth along <0001>, <10‐10>, and <11‐20>.…”
Section: Resultsmentioning
confidence: 99%
“…The emission spectra from each of the facets are relative to the nonpolar facet and reveals that the peak emission is more than an order of magnitude more intense than from the other facets and dominates the nanorod emission. The brighter intensity from the non-polar sidewalls may arise from the mitigation of the internal electric fields leading to stronger overlap of the electron and hole wavefunctions as well as from the optimised growth parameters 25 . The lowest energy emission, at a peak energy 2.48 eV, arises from the polar tips of the nanorods, whilst there is an increase in the peak energy of the emission from the semipolar facets to 2.53 eV.…”
mentioning
confidence: 99%
“…1c prism(1)) is in the base of the nanorod, where only the GaN near band edge (NBE) signal can be detected, showing that no In x Ga 1− x N growth occurred on the m -plane sidewalls during the deposition of the InGaN/GaN active zone. This is expected given the ultradense nature of the array 10 from which the individual rod was extracted and in contrast to nanorods with a wider spacing where In x Ga 1− x N growth could be found on the m -plane 12 , 13 . The small FWHM (113 meV at 300 K) of the GaN NBE peak and the absence of any yellow luminescence on the m -plane sidewalls indicate that damage introduced during the etching process was successfully healed during the regrowth and the material is of high optical quality 14 17 .…”
Section: Resultsmentioning
confidence: 99%
“…2a ). This is most likely caused by the extinction of a -plane facets during the regrowth 13 , 18 .
Figure 2 Intensity plots of the emission GaN NBE emission ( a ), the semipolar QW emission between 395 nm and 480 nm ( b ), and the emission observed from the apex of the nanorod from 490 nm to 650 nm ( c ).
…”
Section: Resultsmentioning
confidence: 99%